Hubungan Kenaikan Berat Badan dengan Kejadian Preeklamsia pada Ibu Hamil di Puskesmas Wilayah Kabupaten Banyumas - Galih Sekar Wangi; Wilis Dwi Pangesti; Ina Rahayu Sakti (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2023)
Preeclampsia in Indonesia is the second leading cause of maternal death after bleeding with an incidence rate of 3-10%. Preeclampsia is the leading cause of death and complications among pregnant women globally. The risk of preeclampsia increases as the mother's weight increases during pregnancy. The purpose of this study was to determine the relationship between weight gain and the incidence of preeclampsia at the Banyumas Regency Health Center. This study used a casecontrol design. The results of this study showed that most respondents in the case group (preeclampsia) had an increase in weight during pregnancy in the abnormal category (weight ≥12.5 kg) as many as 66 respondents (66%) and in the control group (not preeclampsia) had an increase in weight in the normal category (weight <12.5 kg) as many as 97 respondents (97%). The results of the McNemara test stated that the proportion of weight gain ≥12.5 kg in the case group (preeclampsia) was 66% and the proportion of weight gain ≥12.5 kg in the control group (not preeclampsia) was 1% so that the difference in the proportion of weight gain ≥12.5 kg in the case group and control group was 65%. There is a relationship between weight gain and the incidence of preeclampsia in pregnant women at the Banyumas Regency Health Center with a p-value of <0.0001 (p-value ≤ α).